Pengaruh Budaya Dalam Tradisi Jawa Terhadap Kehidupan Sehari-Hari Pada Masyarakat di Desa Aek Korsik - Ainun Jawahir; An'nas Tasya Rahmadhani; Rani Ramadani; Zulfadli Lingga (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Thel purposel of thils study was to deltelrmilnel thel procelss of assilmillatilon of Javanelsel culturel wilth othelr culturels iln Samarilnda Cilty, to filnd out thel salvatilon tradiltilon iln aelk korsilk Cilty, to deltelrmilnel thelilnfluelncel of culturel and tradiltilon on dailly lilfeliln aelk korsilk Cilty. Thel relselarch melthod useld ils delscrilptilvel qualiltatilvel relselarch. Iln thils study, relselarchelrs willl usel documelnts, liltelraturel from books, journals and elssays as sourcels of data. Iln addiltilon, thel author also conducteld ilntelrvilelws whilch latelr can bel useld as supportilng data iln thils study. Thel relsults of thel study ilndilcatel that thelilnfluelncel of Javanelsel culturel and tradiltilons on peloplel's dailly lilvels has a posiltilvelilmpact, culturel and tradiltilons such as salvatilon can bel onel of thel lilnkagels beltweleln Javanelsel and non-Javanelsel pelopleliln aelk korsilk Cilty. Iln addiltilon, thel crelatilon of harmony ils also born from thel accelptancel of culturel and tradiltilons by non-Javanelsel relsildelnts, Javanelsel culturel and tradiltilons arelelasy for thelm to accelpt and do. Thils relselarch ils elxpelcteld to add ilnsilght ilnto knowleldgel about thelilnfluelncel of Javanelsel culturel and tradiltilons for thel communilty, elspelcilally iln aelk korsilk Cilty to mailntailn elxilstilng tilels of frilelndshilp and harmony so that Javanelsel and non-Javanelsel peloplel lilvilng iln Samarilnda Cilty arel not dilvildeld belcausel of unnelcelssary conflilcts.